Codelivery of Doxorubicin/PI3K Inhibitor Nanomicelle Linked with Phenylboronic Acid for Enhanced Cytotoxicity to Pancreatic Cancer. (23rd June 2022) - Zeng, Xuan; Fan, Xiaoxiao; Fu, Chunyan; Yang, Jialu; Tian, Jiahui; Peng, Qian; Qin, WeiGuo; Wu, Yi
Abstract : Multidrug combination therapy for pancreatic cancer is widely applied in clinical practice. In this study, we used phenylboronic acid and polyethylene glycol as materials of nanomicelles, loaded with the PI3K/mTORC1 dual inhibitor PF04691502 (PF) to inhibit the resistance and metastasis of pancreatic cancer and increase the sensitivity of doxorubicin (DOX). We prepared the PPD nanoparticles (NPs) with a small PDI and a uniform morphology by controlling the DOX substitution degree (size of 164.8 ± 3.6  nm and zeta potential of − 16.9 ± 0.4  mV). We determined the rates of PF and materials through the combination experiment of free drugs and the obtained PF@PPD NPs (size of 200.8 ± 2.6  nm and zeta potential of − 13.9 ± 0.3  mV). The drug loadings of DOX and PF in the nanomicelle were 14.8 ± 0.4 % and 9.5 ± 0.3 %, respectively. And the drug release in vitro was slow (29.17 ± 2.00 % for DOX and 39.22 ± 2.49 % for PF). The cell assay showed that the NPs had a good curative effect and migration on BxPC-3 cells, and it could be continuously taken up by cells. The PF@PPD NPs displayed a dose-dependent cytotoxicity with less cell viability (20.38 ± 1.11 % ) and higher uptake in BxPC-3 cells compared with the free drug. The combined medication or PF@PPD NPs reduced tumor metastasis, indicating that PF@PPD NPs had the potential for clinical application.